RAW RESOURCES’ FORMATION RESEARCH IN THE BUSINESS PROCESS OF RUBBER PRODUCTION - V. V. Aleshchenko; I. A. Eychler (Вестник СибАДИ)
Introduction. The paper presents the thesis about the advantages of the process approach in the development of measures aimed at improving the efficiency of rubber products, using rubber-containing waste as raw materials. In addition, the insufficiency of existing approaches to the definition of business processes using typical raw materials, on the basis of which the author’s definition of the business process is proposed, is substantiated. The main approaches to improving the efficiency of such business processes is formulated, defined on the construction of the participants’ interaction system to meet their basic requirements. Moreover, the importance of studying the information space is highlighted, in which the formation of business processes is displayed.Materials and methods. The research of the influence of information space on the formation of business processes for the production of rubber is carried out on the basis of such methods as the analysis of industry statistics, the study of legal acts that determine various aspects of the functioning of production and economic systems. The determination of the current state of the information space requires the research of materials of the state statistics service, marketing agencies and large enterprises of the rubber industry, using worn rubber products as raw materials. The requirements of suppliers of raw materials are also determined by an expert survey.Results. As a result, the list of the main participants and the main requirements are identified. The authors show the significant impact of the resource factor on the efficiency of business processes for the rubber production. Therefore, The authors present the model of the participants’  interaction at the stage of collecting raw materials.Discussion and conclusions. The list of the main factors hindering the development of the rubber products production is determined and ways to overcome the negative impact of factors by reviewing the mechanism of the business processes formation are considered.